Efektivitas Model Pembelajaran Kooperatif STAD dalam Mengoptimalkan Prestasi Belajar IPA Siswa Kelas V di sekolah Dasar - Hidayati, Isnah; Fajrie, Nur; Fathurohman, Irfai (Journal Prakarsa Paedagogia, 2024)
The challenge in elementary science education often lies in the complexity of topics such as the Human Digestive System, posing difficulties for student comprehension. This study investigates the efficacy of cooperative learning, particularly the Student Teams Achievement Division (STAD), in enhancing science learning outcomes for Grade V students at SDN 1 Panggang Jepara. Utilizing the Classroom Action Research method, the study designs, implements, observes, and reflects on the learning process through iterative cycles. Data collection involves observation sheets, formative tests, and documentation for evaluation. Results indicate a substantial rise in average student scores, from 61 pre-cycle to 86 in the subsequent cycle following STAD implementation. Mastery levels increased from 33% initially to 89% after the intervention. These findings affirm STAD's effectiveness in improving student comprehension of scientific content, fostering active engagement in collaborative learning, and offering practical insights for educators to enhance teaching quality.